The Impact of Zakah, Islamic Bank, Macroeconomic Variables on Unemployment Rate: Evidence From Selected OIC Countries - Rusanti, Ega; Sekar Sari, Novi; Rusgianto, Sulstiya; Ahmed, Ishfaq (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
The Organization of Islamic Cooperation (OIC) countries have experienced a significant increase in the unemployment rate, and some countries even have the highest unemployment rate in the world. This study aims to examine the effect of zakah, Islamic Bank, and macroeconomic variables consisting of economic growth, inflation and trade openness on the unemployment rate the Organization of Islamic Cooperation (OIC) members. The annual data on 40 OIC countries from 2012 to 2021 is employed on this research. The result shows that zakat and banking do not give significant influence on the reduction of unemployment rate while other macroeconomic variables have significant effect. This research can provide practical implications for decision makers, especially the government, to evaluate policies on zakat and Islamic banking so that they can influence the reduction of unemployment as well as other macroeconomic variables in OIC countries